A Mysterious DRESS Case: Autoimmune Enteropathy Associated with DRESS Syndrome. (26th November 2017) - Adike, Abimbola; Boppana, Vaishnavi; Lam-Himlin, Dora; Stanton, Melissa; Nelson, Steven; Ruff, Kevin C.
Abstract : Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) is a rare but potentially life-threatening cutaneous hypersensitivity reaction characterized by extensive mucocutaneous eruption, fever, hematologic abnormalities, and extensive organ involvement. Here, we present a case of a young woman with DRESS syndrome following exposure to vancomycin with renal, cutaneous, and gastrointestinal involvement. To the best of our knowledge, this is the first case description in the literature of DRESS of the gastrointestinal tract with autoimmune enteropathy.